Influence of Dieletric Constants on Complex Equilibra of Sm(III)-Captopril in Dioxane-Water Mixtures - Vighe, D.S. (Asian Journal of Chemistry, 2010)
The interaction between Sm(III) and captopril in differentpercentage of dioxane-water mixtures at 0.1 M strength and27 ± 0.1 ºC has been studied pH-metrically. The dataobtained can be used to evaluate the proton-ligand and metalligandstability constants for 1:1 and 1:2 complexes. Theeffect of dielectric constants on the stability of complex equilibriumis also studied.